Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer’s Disease - Nunez, Kavin (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer’s disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS’s inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.